In Vitro Immunomodulatory Activity of Fig Fruit Ethanol Extract (Ficus carica Linn) against Phagocytosis Macrophages and Lymphocyte Proliferation - Iis Nur Azizah; Aji Winanta (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Fig (Ficus carica L.) is a natural product that potentially can improve the immune system because it has flavonoids that have the potential as immunostimulants. The research aims to determine the possibility of fig fruit ethanol extract as an immunomodulator. Immunomodulatory activity is determined by knowing the activity of macrophage phagocytosis and lymphocyte proliferation in vitro and the levels of flavonoids in the extract. The research began with extraction, and then the sample was tested with TLC and colorimetry methods. Furthermore, the sample in the immunomodulatory activity test in vitro was measured through the activity of macrophage phagocytosis and lymphocyte proliferation. In the phagocytosis activity test, macrophage cells were given samples in various concentrations and latex beads. The number of activated macrophages and the number of latex phagocyted by the macrophage is then calculated. For tests of lymphocyte proliferation activity, lymphocyte cells were sampled with different concentrations and induced hepatitis B vaccine. Then the cell absorbance was read with an Elisa reader at 550nm wavelength. The study results found that the samples contained flavonoid compounds, and the total flavonoid levels obtained were 0.74±0.01 mgEQ/g samples. The immunomodulatory activity showed that the sample increased phagocytosis activity of macrophages compared to cell control. The lymphocyte proliferation test produced stimulation index<2 values, showing no effect on the proliferation of lymphocytes. This study indicated that fig fruit ethanol extract could increase the phagocytosis activity of macrophage cells but did not affect the proliferation of lymphocyte cells in vitro.